METHODS OF USING WHEAT BRAN IN THE TREATMENT OF SOME DISEASES (Scientific journal of the Fergana State University, 2024)
In the article, we analyzed healing methods due to the fact that disruption of physiological processes in the human body leads to illness in our body at different levels and the rational use of different bran samples. Inflammation is divided into acute and chronic types. Acute inflammation occurs when the body mounts an immune response to fight an infection or injury. Acute inflammation is localized and indicates a healthy immune system. Chronic inflammation is inflammation that occurs over a long period of time. Inflammatory diseases, considered the most common, are directly related to the activity of the immune system. In folk medicine and medicine, in addition to various bran cereals, its products prepared with curdled milk or milk, honey, beets and apricots are used in the treatment of diabetes, constipation (constipation), excess weight, liver and biliary tract diseases, and kidney diseases. . is known to be used. We would like to offer various methods of application and treatment of such types of internal inflammatory diseases as Crohn's disease, atherosclerosis and weakening of the immune system due to the antioxidant activity of bran, which is a waste product of cereal plants, and the action of its biological properties. active substances.